Risk factors for SARS-CoV-2 infection among health workers in India: a case control study - Leyanna Susan George; Leyanna Susan George; Chitra Tomy; Charutha Retnakumar; Uday Narlawar; Pankaj Bhardwaj; Jayasree Krishnan; R. L. Lakshman Rao; Prakash Patel; Anil S. Bilimale; Poornima Baby; Minu Maria Mathew; et al. (Frontiers Media S.A., 2023)
BackgroundCOVID-19 was declared as a Public Health Emergency of International Concern on 30th January 2020. Compared to the general population, healthcare workers and their families have been identified to be at a higher risk of getting infected with COVID-19. Therefore, it is crucial to understand the risk factors responsible for the transmission of SARS-CoV-2 infection among health workers in different hospital settings and to describe the range of clinical presentations of SARS-CoV-2 infection among them.MethodologyA nested case-control study was conducted among healthcare workers who were involved in the care of COVID-19 cases for assessing the risk factors associated with it. To get a holistic perspective, the study was conducted in 19 different hospitals from across 7 states (Kerala, Tamil Nadu, Andhra Pradesh, Karnataka, Maharashtra, Gujarat, and Rajasthan) of India covering the major government and private hospitals that were actively involved in COVID-19 patient care. The study participants who were not vaccinated were enrolled using the incidence density sampling technique from December 2020 to December 2021.ResultsA total of 973 health workers consisting of 345 cases and 628 controls were recruited for the study. The mean age of the participants was observed to be 31.17 ± 8.5 years, with 56.3% of them being females. On multivariate analysis, the factors that were found to be significantly associated with SARS-CoV-2 were age of more than 31 years (adjusted odds ratio [aOR] 1.407 [95% CI 1.53-1.880]; p = 0.021), male gender (aOR 1.342 [95% CI 1.019-1.768]; p = 0.036), practical mode of IPC training on personal protective equipment (aOR 1. 1.935 [95% CI 1.148-3.260]; p = 0.013), direct exposure to COVID-19 patient (aOR 1.413 [95% CI 1.006-1.985]; p = 0.046), presence of diabetes mellitus (aOR 2.895 [95% CI 1.079-7.770]; p = 0.035) and those received prophylactic treatment for COVID-19 in the last 14 days (aOR 1.866 [95% CI 0.201-2.901]; p = 0.006).ConclusionThe study was able to highlight the need for having a separate hospital infection control department that implements IPC programs regularly. The study also emphasizes the need for developing policies that address the occupational hazards faced by health workers.